Identifying High Growth Firms in India: An Alternative Approach - Aradhna Aggarwal; Takahiro Sato (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2015)
Over the past two decades, considerable interest has grown in high growth firms (HGFs). However, the concept of HGFs still remains controversial. One of the most controversial issues is size and age of these firms. The present study argues that the current literature on HGFs may offer little help in addressing this issue given the constantly changing population of HGFs. This study uses an alternative conceptual framework and proposes a concept of 'High Impact Group of Firms' (HIGF). It explains the HIGFs in the framework of a new stream of literature that focuses on business dynamics, productivity growth and industry evolution, formulates testable hypotheses, and uses a novel methodology to identify it. The empirical analysis is based on the plant level panel data of 22 manufacturing industries in Indian manufacturing during the period 2000-01 to 2005-06. Our empirical results reveal that much depends on the industry/sector specific characteristics.
hdl:10398/9119
Keywords: 330; High growth firms; India; Productivity growth; Business dynamics; Decomposition; Produktivitätsentwicklung; Unternehmenserfolg; Dekompositionsverfahren; Industrie; Indien